DNA methylation profiling of CpG islands in trigeminal ganglion of rats with orofacial pain induced by experimental tooth movement - Yafen Zhu; Liqun Gu; Jian Wang; Jie Han; Junzhuo Gou; Zhifang Wu (BMC Oral Health)
Abstract Background Tooth movement induced orofacial pain is the most cited negative effect during orthodontic treatment, while treatment options without side effects are limited. The differential expression of pain-related genes due to DNA methylation and demethylation is instrumental in pain. The purpose of the study was to evaluate the DNA methylation profiling of CpG islands (CGI) and CGI shores in promoter regions in trigeminal ganglions (TG) of tooth movement induced orofacial pain rats, thus to further insight the DNA methylation regulation in orofacial pain. Materials and methods An orofacial pain rat model was constructed by ligating coil springs between the incisor and first maxillary molar with 40 g of force. The Rat Grimace Score (RGS) was used for pain evaluation. The genome methylation status was analyzed by the reduced representation bisulfite sequencing (RRBS) technique. Gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG) analyses were conducted in the differentially methylated regions (DMRs). Moreover, a protein-protein interaction (PPI) network was established to detect annotated genes associated with pain. Results RGS was significantly higher in orofacial pain rats than in sham rats. RRBS showed widespread methylation changes in CGI and CGI shores in TG promoter regions. Both 902 hypermethylated DMRs and 862 hypomethylated DMRs were found in the CGIs of promoter regions. KEGG analysis revealed that annotated genes are participated in endocrine, nervous, immune, and sensory systems. Moreover, the “Calcium signaling pathway”, “Wnt signaling pathway” and “Neuroactive ligand-receptor interaction” were significantly enriched pathways. Furthermore, PPI network showed several genes (Ctnnb1, Dlg4, Creb1, Camk2g, Bmp2, etc.) with different methylation statuses were reported to be associated with pain. Conclusions This study demonstrated methylation changes were existed in CGI and CGI shores in TG promoter regions when pain occurs, thus providing a basis for further study on the mechanism of DNA methylation in orofacial pain.